1971
DOI: 10.1111/j.1365-3180.1971.tb00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Residual Activity of Paraquat in Soils I. Factors Affecting Persistence

Abstract: Phytotoxizitat von Paraquat zu verringern. Die phytotoxischen Ruckstande wurden nicht durch Oberflachenbewasserung verringert, sie verschwanden jedoch bei mechaniseher Bearbeitung der Bodenoberflache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1971
1971
2004
2004

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Weber et al (1965) found that diquat and paraquat were adsorbed to a lesser extent than either 2,4-D or prometon on charcoal. At IO°C paraquat attained equilibrium within I h and diquat within 48 h but at 55°C slow adsorption of both compounds was still continuing after 480 h. Our observations are in agreement with those of Damanakis et al (1970c) who reported that paraquat was available to seedlings well within the SAC of peat soils and reaffirm the previous work of Watkin & Sagar (1971) in which paraquat activity on sprayed surfaces was readily detected on other soil types when application rates were higher. The absence of phytotoxie residues on peat at low doses ofthe herbicide indicates that this soil has a limited capacity to inactivate paraquat, though the mechanism of adsorption may not necessarily be the same as on mineral soils.…”
Section: Experiments 1 the Adsorptive Capacity Of Soilssupporting
confidence: 92%
See 2 more Smart Citations
“…Weber et al (1965) found that diquat and paraquat were adsorbed to a lesser extent than either 2,4-D or prometon on charcoal. At IO°C paraquat attained equilibrium within I h and diquat within 48 h but at 55°C slow adsorption of both compounds was still continuing after 480 h. Our observations are in agreement with those of Damanakis et al (1970c) who reported that paraquat was available to seedlings well within the SAC of peat soils and reaffirm the previous work of Watkin & Sagar (1971) in which paraquat activity on sprayed surfaces was readily detected on other soil types when application rates were higher. The absence of phytotoxie residues on peat at low doses ofthe herbicide indicates that this soil has a limited capacity to inactivate paraquat, though the mechanism of adsorption may not necessarily be the same as on mineral soils.…”
Section: Experiments 1 the Adsorptive Capacity Of Soilssupporting
confidence: 92%
“…The response shown by imbibed grains of Lolium perenne sown on paraquattreated soil surfaces (Watkin & Sagar, 1971) suggested that uptake ofthe herbicide by the grains occurred from the adsorbed and not the desorbed phase in soil. This was also indicated by the apparent failure ofthe herbicide to be leached following surface irrigation in other experiments (see also Damanakis et al, 1970a).…”
Section: Experiments 3 the Desorption Of Paraquat In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Less susceptible were rape, white clover {Trifolium repens L.) and six cultivars of wheat {Triticum vulgare Host.). In earlier work Watkin & Sagar (1971) found phytotoxicity with persistence of at least 14 days in pot experiments with white clover and perennial ryegrass. They found residues, greater on organic soils, to be reduced by soil disturbance after spraying, but not by surface irrigation.…”
Section: Introductionmentioning
confidence: 92%
“…Although paraquat had an immediate effect on the abundance of S. nemoralis, the species actively proliferated in closed communities after paraquat had become inactivated in the soil by absorption (Watkin and Sagar 1971), microbial metabolism (Baldwin et al 1996), or decomposition by ultraviolet light (Slade 1965). Stimulation was also observed in open communities following the application of 2,4-D (Tompkins and Grant 1974).…”
Section: Response To Herbicides and Other Chemicalsmentioning
confidence: 94%